Factibilidad para la creación de una empresa que elabore flores con material reciclado (botellas plásticas) en el cantón Quevedo. Año 2015. - Martínez Bravo, Aida Mariuxi (2015)
This research takes a feasibility study for the establishment of a company producing flowers from recycled material. (Plastic bottles) in the canton Quevedo, 2015 to give the population of the canton Quevedo an alternative when purchasing flowers or ornaments to decorate their homes to determine the demand that will flower market survey method was used the market environment was analyzed using the women population surveys since they are the decision makers when buying ornaments to decorate the home. A technical study which defines the micro localization, requirements, machinery, raw material workmanship infrastructure and project size, also functional and legal organic structure of the company was held, human resources, including with organized technical study requirements have company for to reach the objectives proposed in this research project. Investment will be directed to the acquisition of machinery, equipment and materials necessary to achieve consolidate the production and marketing operations required by the company, the initial investment required for the implementation of the project is $ 12.572,02 according to studies the project is viable, because it reflects the following values an internal rate of return (IRR) of 155% a net present value (NPV) indicating that the project will generate a wealth of $ 96.493,19 over the life of the project cost-benefit ratio is 1.57 which indicates that for every dollar the company invests the investor gets 0,57ctvs Studies obtained in different studies and the assessment made by economic. Indicator shows that the creation of a company producing flowers from recycled materials is feasible. (Plastic bottles) in the cantón Quevedo.